Relation between auditor quality and corporate tax aggressiveness: Implications of cross-country institutional differences - KANAGARETNAM, Kiridaran (Institutional Knowledge at Singapore Management University, 2016)
Using an international sample of firms from 31 countries, we study the relation between auditor quality and corporate tax aggressiveness. Employing an indicator variable for tax aggressiveness when the firm's corporate tax avoidance measure is within the top quintile of each country-industry combination, we find strong evidence that auditor quality is negatively associated with the likelihood of tax aggressiveness, even after controlling for other institutional determinants such as home-country tax system characteristics. We also find that the negative relation between auditor quality and the likelihood of tax aggressiveness is more pronounced in countries where investor protection is stronger, auditor litigation risk is higher, the audit environment is better, and capital market pressure is higher.